Crossing Frontiers: A Comparative Exploration of AI Inventorship and Ownership in Patent Law - Mutale, Chisanga (Tumkur: Sretechjournal Publication, 2025)
This article aims at examining inventorship and ownership of Artificial Intelligence (AI) systems in patent law. This is achieved by employing a comprehensive review of relevant patents Acts, policy documents and cases such as Thaler v. Iancu, case no. 1:20-cv-00903 (E.D. Va). The review is coupled with the analysis of AI inventorship and ownership across various jurisdictions such as the United States of America, European Union and South Africa. This is done to understand the criteria for determining inventorship, ownership and the contemporary interpretations of the concept of “intelligence." The article finds that current patent laws encounter difficulties in adequately protecting AI-generated or assisted inventions due to limitations in recognizing AI as inventors. It is therefore argued that if the current patent system cannot accommodate AI related inventions, then there is urgent need to consider a sui generis system tailored to address the unique challenges posed by AI inventions within patent law. Taken together, the article underscores the need for patent legal frameworks to ensure fair treatment and protection of AI-generated or assisted inventions. The article also notes that there is need for further research for an enhanced understanding of the interplay between AI and patent law.